1994
DOI: 10.1002/jmv.1890420314
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus‐RNAs in plasma and in peripheral blood mononuclear cells of hemophiliacs with chronic hepatitis C: Evidence for viral replication in peripheral blood mononuclear cells

Abstract: Hemophiliacs who have been exposed to unheated and/or dry heated pooled clotting factor concentrates are at high risk of chronic hepatitis C. Although the mechanism and site of hepatitis C virus (HCV) replication are not yet known, HCV is thought to replicate through a complementary negative RNA strand, as has been shown for flaviviruses. The detection of negative RNA strands has therefore been regarded as a marker of replication. We investigated the prevalence of HCV-RNA and of negative HCV-RNA strands in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 26 publications
(7 reference statements)
2
61
0
1
Order By: Relevance
“…In the literature it has been suggested that PBMC can function as an important extrahepatic reservoir and a possible site for HCV replication. The evidence for this assumption was based on the demonstration of negative-strand HCV-RNA in association with PBMC from HCV infected patients by a RT/PCR technique [16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature it has been suggested that PBMC can function as an important extrahepatic reservoir and a possible site for HCV replication. The evidence for this assumption was based on the demonstration of negative-strand HCV-RNA in association with PBMC from HCV infected patients by a RT/PCR technique [16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the hybrid cell clones, IMY-N9, had 98 chro- 6 3 0 10 Ϫ1. 6 3 0 *Necessary HCV-RNA content for 50% tissue culture infection in samples (HCV RNA titer/TCID 50 /mL). †Culture media obtained from HCV in vitro culture system (Ito T, et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…29,[67][68][69][70][71][72] Initial studies similarly reported extrahepatic replication of HCV in PBMCs (Table 3). 58,[73][74][75][76][77] However, as the detection assays were not able to adequately differentiate between positive-and negative-strand HCV RNAs, theses results should be interpreted with extreme caution. Subsequent studies have now convincingly demonstrated negative-strand HCV RNA -albeit in a minority of PBMCs tested -particularly among immunosuppressed patients, such as HIV/AIDS patients 68,69,71 and liver transplant recipients.…”
Section: Evidence For Extrahepatic Replication Of Hcvmentioning
confidence: 99%